Integrating Character Education Elementary Mathematics: A Systematic Review of Values, Pedagogical Strategies and Moral Outcomes - Bisri Musthofa; Hasanah Abd Khafidz; Intan Aulia Rakhmawati; Ahmad Sunoko (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
While character education is widely promoted in elementary curricula, mathematics remains largely conceptualized as a value-neutral domain. Existing studies tend to focus on instructional tools rather than explaining how moral values are formed through mathematical learning processes. This conceptual systematic review synthesizes empirical studies indexed in Scopus and SINTA (2010–2025) to examine the underlying mechanisms through which character education is integrated into elementary mathematics. Using a PRISMA-guided selection and theory-informed synthesis, nine high-quality studies were analyzed. The review identifies recurring patterns of value representation, engagement, reflection, and internalization across narrative, cultural, and contextual pedagogies. Based on this synthesis, the study proposes the Mathematics–Character Integration Mechanism (MCIM) as a conceptual framework explaining how mathematics functions as a moral learning domain. This framework contributes to theoretical advancement by shifting the discourse from instructional techniques to mechanism-based character formation, with implications for curriculum design, teacher education, and future empirical research.